WORK-FAMILY CONFLICT AMONG WORKING STUDENTS: STRATEGIES, CHALLENGES, AND IMPLICATIONS FOR ACADEMIC SUCCESS - Monalisa, Monalisa; Stevani, Hayu; Oktasari, Maria; Dewi, Eka Riyana (Universitas Indraprasta PGRI, 2024)
Learning and working becomes a necessity to improve individual abilities to keep up with the times and the needs of the global industry. Working conditions that demand career development require one to study again at a higher level. this results in roles and responsibilities that are carried out simultaneously. Thus causing conflict. Indonesia has cultural diversity so cultural uniqueness becomes an interesting side in efforts to overcome conflict. This study aims to explore the experiences of individuals who carry out two life roles in terms of their culture. This research is a phenomenological qualitative research. The participants were 5 people who were students and workers (3 Female and 2 Male) with different cultural backgrounds (Javanese, Minang, and Batak cultures), Data were collected through in-depth interviews, analysis technique is the Colaizzi method. Three main themes emerged from the work-family conflict, namely: (1) the family environment has an important role in the progress and resolution of role conflicts with different cultural backgrounds, (2) the work environment causes more conflict, and (3) the campus environment requires more intensive time management compared to other environments. The findings from this study provide insights into how to cope with conflicts while performing dual roles. In addition, this study also underscores the influence of the surrounding environment on such conflicts. By providing a deeper understanding of these experiences, it is hoped that this study will help mitigate the negative impacts associated with performing dual roles in the contemporary professional landscape.